2009
DOI: 10.2320/matertrans.m2009280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Current Density on Elongation of an Electropulsing Treated Zn-Al Based Alloy

Abstract: Effects of static electropulsing on microstructure and elongation of the ZA 22 alloy were studied by using scanning electron microscopy and transmission electron microscopy techniques. It was found that the current density of electropulsing treatment (EPT) was one of the factors that influenced microstructural changes and dislocation structure in the EPT alloy. The identity of the microstructure and the dislocation density played an important role in plastic elongation of the EPT alloy. The effects of the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…A large number of dislocations piled up and blocked at the grain boundaries and at the structural defects, such as dislocations, vacancies, and precipitates, inside the grains, where a great deal of strain energy accumulated. [5][6][7] The energy storage at the grain boundaries and the structure-distorted sites inside the grains varied in accordance with the dislocation movement mechanism. At the grain boundaries, accumulation and annihilation of dislocations occurred at the same time.…”
Section: B the Evolution Of Texture During Recrystallization Under Ementioning
confidence: 94%
See 2 more Smart Citations
“…A large number of dislocations piled up and blocked at the grain boundaries and at the structural defects, such as dislocations, vacancies, and precipitates, inside the grains, where a great deal of strain energy accumulated. [5][6][7] The energy storage at the grain boundaries and the structure-distorted sites inside the grains varied in accordance with the dislocation movement mechanism. At the grain boundaries, accumulation and annihilation of dislocations occurred at the same time.…”
Section: B the Evolution Of Texture During Recrystallization Under Ementioning
confidence: 94%
“…When the intensity of the electropulsing increased to 152 Hz/1023 K (750°C)-EPT, a new balance between the accumulation and the annihilation of the dislocations was established. [6] Both the texture (100)h110i (green in color) and the higher energy stored (111)h112i texture (dark blue in color) vanished. The textures consisted of mainly (111)h110i (color in light blue) and a small amount of G (110)h100i, as shown in EBSD mapping (Figure 4(a3)).…”
Section: B the Evolution Of Texture During Recrystallization Under Ementioning
confidence: 96%
See 1 more Smart Citation
“…The wire specimen was cut into pieces of 100-mm length for static EPT (without external stress affect) at ambient temperature (28°C). A self-made electropulsing generator was applied to discharge positive direction multiple pulses with various current intensities (10,15,20, and 30) for 10 seconds. The frequency of the multiple electropulses was selected as 100 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Previous work by the present authors and co-workers has shown that electropulsing induced phase transformations consisted of two kinds of phase transformations: forward and reverse phase transformations. [6] It was also reported that with adequate dynamic electropulsing, the elongation of the Zn-Al based alloy was increased by 437 pct at ambient temperature under a high strain rate, whereas the instantaneous tensile stress remained unchanged, compared with that of the non-EPT alloy.…”
Section: Introductionmentioning
confidence: 99%